MEASURING PRODUCTIVITY - Xhaferi, Besa (European Scientific Journal, ESJ, 2012)
Productivity may be a growth enhancement in the micro level and macro level. Disputable is how to measure productivity in the sense of variables used as proxies and the methodology used for estimation. In this paper we review methodologies used in productivity measurement. In our research we classify studies that measure productivity in: index number studies (Malmquist index and Törnqvist index), production function studies, distance function studies and DEA analysis. We conclude that the definition of variables used in the model and the estimation methodology are crucial for the results we will obtain. Also we suggest that micro- panel dataset may be helpful in solving estimation and comparison models in productivity studies.